NARRATIVE DESIGN IN SERIOUS GAMES: A FRAMEWORK FOR ENHANCING PLAYER ENGAGEMENT AND LEARNING OUTCOMES IN EDUCATIONAL GAMES - Jari Koskinen; Michael Turner; Sarah Robinson (Journal of Social Entrepreneurship and Creative Technology, 2025)
The integration of narrative design in serious games has become a pivotal factor in enhancing player engagement and improving learning outcomes in educational games. Despite the growing use of game-based learning, the specific role of narrative elements in achieving these outcomes remains underexplored. This research aims to develop a framework for narrative design in educational games, focusing on its impact on player engagement and learning outcomes. A mixed-methods approach was employed, combining quantitative surveys to measure knowledge retention, problem-solving, and critical thinking, with qualitative interviews to explore player experiences and emotional engagement. The study involved 200 participants who were divided into two groups: one playing games with strong narrative elements and the other with minimal narrative content. The results indicate that narrative-driven games significantly enhance engagement and improve learning outcomes. Players in the narrative-heavy group demonstrated higher levels of knowledge retention (M = 4.45), problem-solving (M = 4.38), and player engagement (M = 4.60) compared to the narrative-light group (M = 3.72, M = 3.55, and M = 3.45, respectively). These findings suggest that effective narrative design is essential for maximizing the educational potential of serious games. The study provides actionable insights for game designers and educators to optimize narrative elements in educational games.